(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article provides a comparative analysis of the mechanisms of action of sarin and other organophosphorus inhibitors belonging to the group of highly toxic nerve agents. It focuses on the biochemical and molecular features of the interaction of these compounds with acetylcholinesterase, including the processes of phosphorylation of the enzyme’s active site, the rate and reversibility of inhibition, and the influence of structural differences between the molecules on their toxicokinetics and toxicodynamics. The factors determining the degree of "aging" of the phosphorylated enzyme, the potential for acetylcholinesterase reactivation by oximes, and the effectiveness of antidote therapy are discussed. A comparative analysis of sarin, soman, and VX is provided in terms of their chemical properties, lethality, stability, and rate of penetration into the body. The results of this study provide a deeper understanding of the principles of action of nerve agents and potential approaches to the development of effective protective measures and treatments for exposure to them.